Microfluidic paper analytical device for the chromatographic separation of ascorbic acid and dopamine. Issue 113 (30th October 2015) - Murphy, A.; Gorey, B.; de Guzman, K.; Kelly, N.; Nesterenko, E. P.; Morrin, A.
Abstract : Cellulose-based filter papers were used as base materials to construct microfluidic paper-based analytical devices (μPADs) coupling a separation channel with electrochemical detection. Abstract : Cellulose-based filter papers were used as base materials to construct microfluidic paper-based analytical devices (μPADs) coupling a separation channel with electrochemical detection. Channel widths were defined by hydrophobic wax, and gold-sputtering through a mask was used to pattern an electrochemical cell at the end of the channel. The physical properties and surface chemistries of various filter papers were studied with respect to the separation of ascorbic acid (AA) and dopamine (DA). Both porosity as well as the ion-exchange capacity of the filter papers were found to influence the separation. Under the conditions used, Whatman grade P81 strong cation exchange paper based on cellulose phosphate was found to fully retain DA. Detection of both AA and DA was achieved on the other filter papers, however, different behaviours were observed. Whatman 4 could not resolve AA from DA while VWR 413 could achieve baseline separation under the conditions used. Depending on the level of oxidative treatment that they undergo, cellulose papers can have carboxyl groups present on the fibres that can act as sources of ion-exchange sites, thus making these types of papers potentially useful for ion-exchange separations. The ion-exchange capacities of the filter papers were investigated and quantified. It was shown that the ion-exchange properties of the papers evaluated varied dramatically. Furthermore, eluent ionic strength and pH were optimised to achieve a baseline resolution of AA and DA. The limit of detection of DA was 3.41 μM when analysed in the presence of 1 mM AA showing the potential of this μPAD for the detection of catecholamines in biological samples containing high concentrations of AA.